A randomized controlled trial to evaluate self-determination theory for exercise adherence and weight control: rationale and intervention description - Matos Margarida G; Santos Teresa C; Coutinho Sílvia R; Castro Margarida M; Vieira Paulo N; Minderico Cláudia S; Markland David; Silva Marlene N; Sardinha Luís B; Teixeira Pedro J (BMC, 2008)
Abstract Background Research on the motivational model proposed by Self-Determination Theory (SDT) provides theoretically sound insights into reasons why people adopt and maintain exercise and other health behaviors, and allows for a meaningful analysis of the motivational processes involved in behavioral self-regulation. Although obesity is notoriously difficult to reverse and its recidivism is high, adopting and maintaining a physically active lifestyle is arguably the most effective strategy to counteract it in the long-term. The purposes of this study are twofold: i) to describe a 3-year randomized controlled trial (RCT) aimed at testing a novel obesity treatment program based on SDT, and ii) to present the rationale behind SDT's utility in facilitating and explaining health behavior change, especially physical activity/exercise, during obesity treatment. Methods Study design, recruitment, inclusion criteria, measurements, and a detailed description of the intervention (general format, goals for the participants, intervention curriculum, and main SDT strategies) are presented. The intervention consists of a 1-year group behavioral program for overweight and moderately obese women, aged 25 to 50 (and pre-menopausal), recruited from the community at large through media advertisement. Participants in the intervention group meet weekly or bi-weekly with a multidisciplinary intervention team (30 2 h sessions in total), and go through a program covering most topics considered critical for successful weight control. These topics and especially their delivery were adapted to comply with SDT and Motivational Interviewing guidelines. Comparison group receive a general health education curriculum. After the program, all subjects are follow-up for a period of 2 years. Discussion Results from this RCT will contribute to a better understanding of how motivational characteristics, particularly those related to physical activity/exercise behavioral self-regulation, influence treatment success, while exploring the utility of Self-Determination Theory for promoting health behavior change in the context of obesity. Trial Registration Clinical Trials Gov. Identifier NCT00513084